Finite element simulation of the T-shaped ECAP processing of round samples. (11th May 2018) - Ghazani, Mehdi Shaban; Fardi-Ilkhchy, Ali; Binesh, Behzad
Abstract: Grain refinement is the only mechanism that increases the yield strength and toughness of the materials simultaneously. Severe plastic deformation is one of the promising methods to refine the microstructure of materials. Among different severe plastic deformation processes, the T-shaped equal channel angular pressing (T-ECAP) is a relatively new technique. In the present study, finite element analysis was conducted to evaluate the deformation behavior of metals during T-ECAP process. The study was focused mainly on flow characteristics, plastic strain distribution and its homogeneity, damage development, and pressing force which are among the most important factors governing the sound and successful processing of nanostructured materials by severe plastic deformation techniques. The results showed that plastic strain is localized in the bottom side of sample and uniform deformation cannot be possible using T-ECAP processing. Friction coefficient between sample and die channel wall has a little effect on strain distributions in mirror plane and transverse plane of deformed sample. Also, damage analysis showed that superficial cracks may be initiated from bottom side of sample and their propagation will be limited due to the compressive state of stress. It was demonstrated that the V shaped deformation zone are existed in T-ECAP process and the pressing load needed for execution of deformation process is increased with friction.